Bringing North Korea to the negotiating table: unstable foundations of Kim Jong-un's North Korean regime. (30th October 2019) - Daekwon, Son
Abstract: This article investigates the linkage between Kim Jong-un's power consolidation and Pyongyang's abrupt return to the denuclearization negotiation table in 2018. It argues that behind Pyongyang's turnabout lie the three unstable pillars of the Kim family's rule: a faithful winning coalition, the juche ideology, and Chinese patronage. Upon taking office in 2011, Kim had to debilitate his father's winning coalition to consolidate his power. With the winning coalition enervated, Kim could not expect its willingness to suppress the masses were they to develop into an ejectorate, and therefore introduced market reforms to secure the people's support. The reforms, in return, inevitably eroded the ideological appeal of the Kim family, thereby rendering his hold on power more vulnerable to economic pressure. Under such circumstances, Chinese patronage increasingly faltered. It is due to the instability of these three pillars that Kim Jong-un returned to the negotiating table.